IMPLEMENTASI PERDA NOMOR 1 TAHUN 2012 TENTANG KAWASAN TANPA ROKOK DI KOTA BUKITTINGGI ( Studi Pada Angkutan Umum ) - Alam Syahuri; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Alam Syahuri, Nim: 1201135119. Implementation Regulation No. 1 Year 2012 on Smoking Area In Bukittinggi. (Study on Public Transportation). Guided by Zulkarnaini,S.Sos,.M.SINo Smoking Area establishment on Public Transportation was an act as protection for the people to the risk of healt problems for effect smoking act absorbed that purposely or involuntary. No smoking area has to be implemented at health facility, school, playground, worship pleace, office, and other public places. In fact,the offenders of on smoking area was not yet gave strict punishment, bad suggestion and lead to offender. This could be seen on many chauffeur and passenger to smoking area on public transportation.The porpose of this research was to analize implementation Non Smoking Area in Bukittinggi city and to know the influenced factor.This research using Van Meter Van Horn theory.The result of this research shows that implementation non smoking area in bukittiggi city (Study on Public Transportation) not totality implemented yet eventhough it already has clear standars, goals, and objectives. Human resource the monitoring of non smoking area team is clear. Coordination and communication between government agency running well and the execution of task fit in with the regulation. Factors that become an obstade in the implementation is less by action smoking area supervisory team and civil service police uni.Keyword : implementation cigarette, No Smoking Area